(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2018)
The site I chose to reflect on is Murramarang beach. This is an important place when thinking about Aboriginal political history, as it depicts life prior to colonisation but was also significant during colonisation. Murramarang would have been the carinya (‘happy home’) to either a single tribe or a meeting place between surrounding tribes, but my connection to this land lies in it being my second place of home.